2014
DOI: 10.1159/000368470
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Spironolactone in Combination with Angiotensin-Converting Enzyme Inhibitors or Angiotensin Receptor Blockers in Patients with Proteinuria

Abstract: Background/Aims: This study aimed to investigate the potential beneficial anti-proteinuric effect of an add-on aldosterone blockade and the impact of the aldosterone escape phenomenon. Methods: We retrospectively analyzed data of 304 patients with persistent proteinuria, who were administered spironolactone (25 mg/day) after treatment with angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin II receptor blockers (ARBs) for >3 months. Patients were divided according to their aldosterone levels during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The incidence rate of severe hyperkalemia was about 6.5% in patients with an eGFR < 60 mL/min/1.73 m 2 , but zero in patients with eGFR ≥ 60 mL/min/1.73 m 2 during dual RAAS-blockade with ACEi or ARB plus spironolactone. These data suggest that spironolactone-associated severe side effects (such as hyperkalemia) are more likely to occur in patients with CKD stages 3 and 4 [19]. In addition, dual RAAS-blockade with spironolactone resulted in a significant drop in blood pressure (−7 mmHg diastolic, −12 mmHg systolic blood pressure), loss of eGFR (−9.3 mL/min/1.73 m 2 ) and a significant decrease of albuminuria (−57%) in diabetic patients after 24 weeks of treatment with spironolactone on top of ACEi or ARB [20].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The incidence rate of severe hyperkalemia was about 6.5% in patients with an eGFR < 60 mL/min/1.73 m 2 , but zero in patients with eGFR ≥ 60 mL/min/1.73 m 2 during dual RAAS-blockade with ACEi or ARB plus spironolactone. These data suggest that spironolactone-associated severe side effects (such as hyperkalemia) are more likely to occur in patients with CKD stages 3 and 4 [19]. In addition, dual RAAS-blockade with spironolactone resulted in a significant drop in blood pressure (−7 mmHg diastolic, −12 mmHg systolic blood pressure), loss of eGFR (−9.3 mL/min/1.73 m 2 ) and a significant decrease of albuminuria (−57%) in diabetic patients after 24 weeks of treatment with spironolactone on top of ACEi or ARB [20].…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, lower aldosterone levels in older Alport mice on dual therapy are the likely cause for improved kidney structure and function. However, Kim and coworkers reported that proteinuria reduction was not associated with the serum aldosterone concentration and add-on spironolactone treatment was more effective in the aldosterone non-escape group compared to the aldosterone escape group of CKD patients [19]. Recently, spironolactone was reported to be able to ameliorate endothelial dysfunction through intracellular oxidative stress attenuation in a 5/6 nephrectomy rat model [27].…”
Section: Discussionmentioning
confidence: 99%
“…Outside of its cardiovascular benefit, [31][32][33][34][40][41][42] some data suggest spironolactone may also slow the progression of CKD. 29,36,37,39,41,[43][44][45][46][47] We observed a marked increase in the incidence of primary safety outcomes in patients with spironolactone use at lower eGFRs, but routine monitoring of SCr and K is warranted at all levels of kidney function. With a better understanding of spironolactone's safety profile in heart failure, ideal candidates for spironolactone can be chosen with the risks for hyperkalemia and AKI balanced accordingly.…”
Section: Discussionmentioning
confidence: 92%
“…During the period from May 2013 to June 2014, a total of 54 consecutive participants (36 men, 18 women; age range, 19-74 years; mean age, 53.22 AE 13.95 years) were recruited into this study. They were admitted with symptoms of swelling, foamy urine, fatigue, poor appetite, or trouble sleeping, and they fulfilled the inclusion criteria of persistent (more than 3 months) albuminuria or micro-albuminuria (7,8). Exclusion criteria were as follows: (i) could not tolerate magnetic resonance imaging (MRI) examination; (ii) presence of other kidney lesions; (iii) metal implants in body; (iv) inability to hold breath for more than 13 s; (v) age less than 18 years; and (vi) acute renal injury (9).…”
Section: Materials and Methods Participantsmentioning
confidence: 99%